Linking school and community - Pantin, Gerard, Fr. (Bernard Van Leer Foundation, 1974)
A small organization of volunteers in Trinidad and Tobago created nursery schools for children of disadvantaged groups in 1971. The use of community resources was stressed, as well as the importance of preprimary education and the role of school community relationship. In this experiment, every effort was made to avoid interference with local cultural forms. The primary school teachers belong to the community; supervisors are responsible for inservice training; parent participation is looked for. The whole curriculum is planned to draw upon local resources. Preschool education, considered as a base for all educational programmes for community development, is associated to parent education programmes informing adults of the needs of children--many have medical and nutrition problems. Effective communication with all members of the community has been established. The imparted values correspond to the local cultural background
Keywords: SERVOL